The cardiovascular toxicity of antimalarial drugs - Chan, XHS (2019)
Malaria is an ancient mosquito-borne parasitic disease from which over a thousand – mostly children in sub-Saharan Africa – still die of needlessly every day. For half a millennium, quinine and quinine-like antimalarial drugs have been the mainstay of malaria treatment and prevention. In the 18th century, the chance observation of their ability to quell palpitations led to their becoming the first anti-arrhythmic agents. Some of these anti-arrhythmic antimalarials later came to define the adverse drug reaction of repolarisation-related cardiotoxicity as sudden deaths, ventricular tachyarrhythmias, and electrocardiographic QT interval prolongation were in turn causally associated with their use. With increasing population-level use of antimalarials for malaria elimination, there has been renewed global interest in defining the cardiovascular toxicity of key members of this drug class to guide antimalarial choice and dosage for development and deployment.